Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1177/075910638400200105
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking Directorates in the Top U.S. Corporations

Abstract: Dans l'introduction, l'auteur présente le problème de l'étude des conseils de direction des grandes compagnies américaines par l'analyse des réseaux. En effet, l'emploi le plus courant d'un membre d'un conseil de direction d'une compagnie est celui de directeur du conseil d'une autre compagnie. L'étude de cette question s'est limitée jusqu'ici à des sous-ensembles préalablement choisis de la population des grandes compagnies. Ce type d'étude, en outre, s'est presque toujours basé sur une orientation théorique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Many authors have stressed the complementarity between these approaches (Koenig and Gogel, 1981;Scott, 1985;Stokman et al, 1988). In combination, they depict corporate interlocks as "traces of power" (Helmers et al, 1975, cited in Fennema andSchijf, 1978) of two sorts: the instrumental power associated with the accumulation of capital and the expressive power associated with class hegemony (Carroll, 2004;Sonquist and Koenig, 1975 …”
Section: Debates Within the Study Of Interlocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have stressed the complementarity between these approaches (Koenig and Gogel, 1981;Scott, 1985;Stokman et al, 1988). In combination, they depict corporate interlocks as "traces of power" (Helmers et al, 1975, cited in Fennema andSchijf, 1978) of two sorts: the instrumental power associated with the accumulation of capital and the expressive power associated with class hegemony (Carroll, 2004;Sonquist and Koenig, 1975 …”
Section: Debates Within the Study Of Interlocksmentioning
confidence: 99%
“…The outstanding study from that era is Sonquist and Koenig's (1975) clique analysis of the American network circa 1969. Geocoding each corporation by the city of its headquarters, they found a structure of 32 overlapping cliques and their satellites, most of which were based in particular cities, with New York hosting the largest and most central group.…”
Section: Spatialitymentioning
confidence: 99%
“…The four quadrants of the figure complement specific theoretical perspectives and empirical traditions. Sonquist and Koenig already noticed that 'we may not require one, but several explanatory models (…) There is no reason why one model should be asked to explain all of [the board interlocks]' (Sonquist and Koenig 1975). Here the emphasis will mainly lie with the relational view on firms and on the corporate elite; the right hand side of figure 1.1.…”
Section: The Social Organisation Of Corporate Governance Networkmentioning
confidence: 99%
“…The accumulation of many corporate board positions by the corporate elite has led to concerns about the concentration of too much (positional) power in the hands of a few. Concentration of (economic) power by means of board interlocks remained topical throughout the twentieth century (Davis 1996;Dooley 1969;Haunschild 1993;Levine 1972;Means 1939;Mintz and Schwartz 1981;Palmer 1983;Pennings 1980;Sonquist and Koenig 1975;Sweezy 1953;Useem 1984). Some early research already revealed patterns of interlocking directorates.…”
Section: Corporate Communities Governance and Control Introductionmentioning
confidence: 99%
“…Using the earlier work of Duncan Luce, he introduced the notion of sociometric cliques. Sonquist used his programs in a seminal article he wrote with Thomas Koenig (Sonquist and Koenig 1975), which they published in a special issue of The Insurgent Sociologist, which Bill Domhoff edited in 1975. The earlier work of Tom Koenig and John Sonquist was already in circulation in 1973 (Koenig et al 1973).…”
Section: Uc At Santa Cruz and Santa Barbaramentioning
confidence: 99%